2012
DOI: 10.1371/journal.pgen.1003150
|View full text |Cite
|
Sign up to set email alerts
|

Systems Genetic Analysis of Osteoblast-Lineage Cells

Abstract: The osteoblast-lineage consists of cells at various stages of maturation that are essential for skeletal development, growth, and maintenance. Over the past decade, many of the signaling cascades that regulate this lineage have been elucidated; however, little is known of the networks that coordinate, modulate, and transmit these signals. Here, we identify a gene network specific to the osteoblast-lineage through the reconstruction of a bone co-expression network using microarray profiles collected on 96 Hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 70 publications
2
63
0
Order By: Relevance
“…Of the other 20 modules, Bicc1 was also highly correlated with the module 9 (M9) eigengene (r = 0.45; P = 2.9 × 10 -6 ) ( Figure 3D). This was not unexpected, because like the M6, we have demonstrated that the M9 is specific to cells of the osteoblast lineage (35). Based on its membership in the M6 and its association with the M9, we measured the expression of the 21 genes in the M6 and the 13 genes in the M9 with "osteoblast differentiation" GO annotations in the 15 HMDP strains that displayed the lowest and highest Bicc1 expression.…”
Section: Figurementioning
confidence: 86%
See 2 more Smart Citations
“…Of the other 20 modules, Bicc1 was also highly correlated with the module 9 (M9) eigengene (r = 0.45; P = 2.9 × 10 -6 ) ( Figure 3D). This was not unexpected, because like the M6, we have demonstrated that the M9 is specific to cells of the osteoblast lineage (35). Based on its membership in the M6 and its association with the M9, we measured the expression of the 21 genes in the M6 and the 13 genes in the M9 with "osteoblast differentiation" GO annotations in the 15 HMDP strains that displayed the lowest and highest Bicc1 expression.…”
Section: Figurementioning
confidence: 86%
“…A full description of the network used to characterize Bicc1 in this study is provided in ref. 35. To generate the coexpression network, we first calculated Pearson's correlation coefficients for all gene-gene comparisons across all microarray samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many independent studies of gene expression patterns during osteoblast differentiation have been described (10,33,44,45), in which apoE was the only apolipoprotein strongly induced during this process (10,33). ApoE regulated bone metabolism in mice is possible due to uptake of lipid and lipid soluble vitamins such as vitamin K into osteoblasts (10).…”
Section: Discussionmentioning
confidence: 99%
“…This process of differentiation has been subdivided into three developmental stages: proliferation, extracellular matrix synthesis and maturation, and mineralization, each of which as characteristic changes in gene expression (8). Many independent studies of patterns of gene expression during osteoblast differentiation have been reported (9)(10)(11), and those studies found that some apolipoproteins were induced during this process (9).…”
Section: Introductionmentioning
confidence: 99%